Managing Business Process Outsourcing - Opportunities & challenges - Meitei, Ch.Ibohal; Balaji, C. D. (Indian Journal of Marketing, 2005)
The paper aims to provide an understanding of Business Process Outsourcing (BPO) and throw light on the opportunities of BPO industry in India and also identify the challenges the Indian BPO companies are facing today. The most commonly outsourced services to the country include professional services like accounting, architecture, customer support, internet research, information processing, marketing, media management, medical transcription and translation services etc. The evolution of BPO in India and the present trend are also described in this paper. A case study of a BPO firm based in Chennai is also incorporated to have an insight into the management of affairs of a BPO company. The paper proposes the possible strategies that the Indian BPO companies can adopt to develop a sustainable growth in this business.